Subversion and sympathy gender, law, and the British novel - Nussbaum, Martha Craven, 1947-; LaCroix, Alison L. (New York : Oxford University Press, 2013)
This interdisciplinary volume of contributed essays focuses on issues of gender in the British novel of the 18th and 19th centuries, particularly Hardy and Trollope. Approaching the topic from a variety of backgrounds the contributors reinvigorate the law-and-literature movement by displaying a range of ways in which literature and law can illuminate one another, and in which the conversation between them can illuminate deeper human issues with which both disciplines are concerned.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Includes bibliographical references and index.
Keywords: English fiction -- 19th century -- History and criticism; English fiction -- 18th century -- History and criticism; Gender identity in literature; Law in literature